Pengaruh Kemudahan dan Manfaat Terhadap Keputusan Penggunaan QRIS Oleh UMKM di Kota Sumbawa - Gina Mailinda Saputri; Handry Sudiartha Athar (Postgraduate, University of Mataram, 2025)
This study aims to test and analyze the influence of convenience and benefits on the decision to use QRIS by MSMEs in Sumbawa City. The sample in this study was 100 samples. The sampling technique in this study used a nonprobability sampling technique with a purposive sampling method. Data analysis in this study used multiple linear regression analysis. All research data was processed using SPSS Statistics 26. The results of statistical data testing and analysis showed that the indicators in the study were declared valid where in the classical assumption test the data was normally distributed and there was no multicollinearity. The results of this study also show that the two independent variables, namely Convenience and Benefits, have a positive and significant influence on the dependent variable, namely the Decision to Use.